Hubungan Tingkat Stress dengan Kecanduan Game Online pada Remaja Umur 15–24 Tahun di Kota Kediri - Forman Novrindo Sidjabat; Muhammad Yudha Tiesnady (KOLONI, 2023)
Previous research adolescents with high stress levels tend to use online games to reduce stress levels, based on data in the City of Kediri the prevalence of residents who experience mental emotional disorders in 2018 is 2,59%. This study aims to analyze the relationship between stress levels and online game addiction in adolescents in the city of Kediri in 2022. This study was a cross sectional study with a sample of 145 adolescent respondents aged 15-24 years in the city of Kediri. Researchers used a google form containing levels of stress and addiction to online games. The research sampling technique is purposive sampling. Results of the study obtained p value of (p: <0,001), so it can be concluded that the level of stress has a significant relationship with online game addiction with a risk effect of 1,5. Conclusion of this study is that stress levels have a significant relationship with online game addiction in adolescents aged 15-24 years in Kediri City. So, adolescents are to use their free time more to do more physical activities and gather with family or those closest to them.